The Validation and Capitalization of the Accounting Truth and of the Aappropiate Image in Accountancy by Means of Financial Audit –Practical Specifics - Mangu (Giurea), Gabriela; Preda (Simion), Alice Mariana; Tegledi, Monica Adriana (Acta Universitatis Danubius. Œconomica, 2022)
The present scientific research is generated by the concern of bringing forth the validation and capitalization of the accounting truth and the appropiate image in accountancy by means of financial auditing, refering to the reforms of these two fields based on the profound changes of the last three decades, but especially of the present ones. The interest and importance of scientific research is enhanced by the researcher's ability to highlight the influence of financial auditing on the credibility of the financial statements of a public interest economic entity in expressing and validating both the accounting truth and the appropiate image of its financial position. Therefore, it finds solutions to users’ requirments as well as to the needs of an efficient management process.